Gintonin modulates platelet function and inhibits thrombus formation via impaired glycoprotein VI signaling. (4th July 2019) - Irfan, Muhammad; Jeong, Dahye; Saba, Evelyn; Kwon, Hyuk-Woo; Shin, Jung-Hae; Jeon, Bo-Ra; Kim, Suk; Kim, Sung-Dae; Lee, Dong-Ha; Nah, Seung-Yeol; Rhee, Man Hee
Abstract: Panax ginseng (P. ginseng), one of the most valuable medicinal plants, is known for its healing and immunobooster properties and has been widely used in folk medicine against cardiovascular diseases, including stroke and heart attack. In this study, we explored the anti-platelet activity of gintonin (a recently discovered non-saponin fraction of ginseng) against agonist-induced platelet activation. In vitro effects of gintonin on agonist-induced human and rat platelet aggregation, granule secretion, integrin αIIb β3 activation, and intracellular calcium ion ([Ca 2+ ] i ) mobilization were examined. Western blot analysis and immunoprecipitation techniques were used to estimate the expression of mitogen-activated protein kinases (MAPKs) and phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) and interaction of glycoprotein VI (GPVI) signaling pathway molecules such as Src family kinases (SFK), tyrosine kinase Syk, and PLCγ2. In vivo effects were studied using acute pulmonary thromboembolism model in mice. Gintonin remarkably inhibited collagen-induced platelet aggregation and suppressed granule secretion, [Ca 2+ ] i mobilization, and fibrinogen binding to integrin αIIb β3 in a dose-dependent manner and clot retraction. Gintonin attenuated the activation of MAPK molecules and PI3K/Akt pathway. It also inhibited SFK, Syk, and PLCγ2 activation and protected mice from thrombosis. Gintonin inhibited agonist-induced platelet activation and thrombus formation through impairment in GPVI signaling molecules, including activation of SFK, Syk, PLCγ2, MAPK, and PI3K/Akt; suggesting its therapeutic potential against platelet related CVD.